Emotions as mediators? Effect of intrinsic motivation on academic performance - Goh, Pamela (2015)
Education is an important field to study, considering the implications it has on people. The present research focuses on the role of emotions in academic settings by examining whether enjoyment, anxiety, boredom and hopelessness mediate the effect of intrinsic motivation on academic performance. If emotions are indeed mediators, elements of academics such as module and class management become critical issues that must be handle well. This includes looking into how classroom delivery and learning materials affect students’ emotions, since their intrinsic motivation towards school are very closely and directly tied to their emotions experienced in school. More importantly, how educators plan for and conduct their modules and classes will influence students’ interest and intrinsic motivation towards their specific modules or school in general, thereby affecting emotions and ultimately academic performance. Building on existing literature review, the present research was based on assumptions that there were significant correlations between I) intrinsic motivation and the four emotions of interest each, II) intrinsic motivation and academic performance, and III) the four emotions each with academic performance. Six Nanyang Technological University undergraduates participated in a questionnaire and a follow-up survey in the present research. Results derived showed no significant correlations between intrinsic motivation, enjoyment, anxiety, boredom and hopelessness on academic performance, as well as between intrinsic motivation and the four emotions. Mediational analyses to test for the presence of mediation by emotions were not carried out subsequently due to the non-significant correlations between variables. Various limitations were identified and recommendations were made for future replications and extensions.